Capturing value from business models: the role of formal and informal protection strategies. (2017) - Bonakdar, Amir; Frankenberger, Karolin; Bader, Martin A.; Gassmann, Oliver
As an overarching concept a business model describes how a firm creates and captures value for itself, its customers, and its partners. Although research has highlighted the importance of value creation and capture of business models, it primarily focused on the value creation mechanisms and neglected aspects of value capturing: until to date, little is known about how firms attempt to protect their business models from competition, which is a critical component of value capture. Drawing on a sample of 24 cases, we explore how business models relate to IP protection mechanisms for value capture and derive a business model protection framework. Our empirical study reveals that the choice of IP protection is contingent on the applied business model. Whereas some razor and blade business models are characterised by a high degree of both formal and informal protection, firms operating franchising business models put higher emphasis on informal protection strategies. Firms running the pay-per-use business model or the multi-sided platform business model apply formal and informal protection strategies to a medium degree in order to capture value. Our findings extend business model literature on novel insights on intellectual property management and also extend the 'profiting from innovation literature' on protection mechanisms in the context of business models.